derivational morphology in modern compound nouns (Abhat Journal, 2025)
This research aims to investigate morphological derivation in modern compound nouns in the Arabic language by analyzing their structural and semantic composition, and comparing them to the traditional system of triliteral and augmented verbs. The study adopted a descriptive-analytical methodology and relied on specialized library-based sources in morphology and linguistics. Findings reveal that modern compound nouns typically do not originate from traditional roots but are rather formed from lexical units arranged in functional combinations to express new meanings. These constructions lie outside the classical derivational framework, despite their widespread use in contemporary Arabic discourse. The comparison also demonstrated that while morphological augmentation in verbs results in systematic semantic expansion, compound structures generate contextual meanings that derive from usage rather than from fixed patterns. The study recommends expanding the theoretical framework of Arabic morphology to include such emerging structures and encourages linking morphological analysis with semantic and contextual interpretation
Keywords: Augmented verbs; Semantic analysis; Contemporary Arabic; Linguistic structure; Morphological development